Effective Multilateralism Through the Looking Glass of East Asia - Prantl, Jochen; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Existing theories of cooperation assume a stable geo-political order, led by countries with a shared conception of the modalities of cooperation. These assumptions are no longer justified. Effective Multilateralism makes the case for a new approach to explaining international cooperation through the lens of East Asian.
Keywords: Science; Science; Science, general